1994
DOI: 10.1037/0022-3514.66.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Causal reasoning in the attribution of rare and common events.

Abstract: Three studies investigated causal reasoning when 2 dispositions-one more common than the other-are both consistently associated with a behavior. Subjects rated the rare disposition as the more important cause when the behavior itself was rare but violated the covariation principle by rating the common disposition as more important when the behavior was relatively common. Results suggest that use of the covariation principle may be the most important heuristic for inferring causality only when the action to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 26 publications
5
31
1
Order By: Relevance
“…These ®ndings parallel Reeder and Brewer's (1979) claim that any cause may explain a moderate or poor performance, whereas an exceptionally good (i.e. extreme) performance points to ability, which is a form of precondition (see also Johnson, Boyd, & Magnani, 1994). These ®ndings with extreme events support the claim that explanations re¯ect the clause that is most abnormal in the circumstances (e.g.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…These ®ndings parallel Reeder and Brewer's (1979) claim that any cause may explain a moderate or poor performance, whereas an exceptionally good (i.e. extreme) performance points to ability, which is a form of precondition (see also Johnson, Boyd, & Magnani, 1994). These ®ndings with extreme events support the claim that explanations re¯ect the clause that is most abnormal in the circumstances (e.g.…”
supporting
confidence: 59%
“…Other studies suggest that extreme events generate attributions to a single extreme cause (Fiedler, 1982 ;McClure et al, 1991 ;Johnson et al, 1994). Morris and Smith (1993) found that with extreme actions, a goal is likely to be insu¬cient and is likely to be accompanied by preconditions such as ability or luck, a ®nding supported by McClure and Hilton (1997).…”
Section: The Control Of Eventsmentioning
confidence: 99%
“…These results deal with predictions rather than explanations, but they are consistent with research showing that explanations of common actions tend to cite goals more than preconditions (e.g. Johnson et al, 1994;Malle, 1999;Malle & Knobe, 1997;Malle et al, 2000;McClure, 2002;McClure & Hilton, 1997, 1998Sutton & McClure, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…Research shows that people usually prefer goals to explain a wide range of common actions, but prefer preconditions to explain actions that are extreme in the sense that they are often not attainable (e.g. Johnson et al, 1994;Lalljee & Abelson, 1983;Leddo & Abelson, 1986;Leddo et al, 1984;McClure, 1998;McClure et al, 1991;McClure & Hilton, 1997;McGill, 1990;N'gbala & Branscombe, 1995;Reeder & Brewer, 1979;Sutton & McClure, 2001). Some causal questions can also lead people to prefer preconditions over goals as explanations (Malle et al, 2000;McClure, 2002;McClure & Hilton, 1998;McClure, Hilton, Cowan, Ishida, & Wilson, 2001).…”
mentioning
confidence: 94%
“…Participants generally were expected to view the atypical antecedent as more predictive of the behavior. Second, consistent with Johnson et al (1994), participants generally were expected to infer that the mental antecedent that was more typical of a target figure was a stronger subjective experience than was the atypical antecedent.…”
Section: Hypotheses For Studymentioning
confidence: 96%